Entre acordes da goianidade: identidade e regionalismos na música goiana (1992-2013) - Santos, Inglas Ferreira Neiva dos (2021)
By understanding that music has a profound relationship with its time, constituting a possible language of expression of the society with which it interacts, the work proposes to understand how a fraction of popular music from Goiás contributes to the narratives of Goianity, having contributed to the Municipal Culture Incentive Laws. For this purpose, we used as a point of reference the Movement of Goianity brought by the Goiana Press Association (AGI) in the early 1990’s, whose main expression was the publication of the magazine “Goianidade” in 1992. Such movement points, among other characteristics, cultural manifestations of a group of singers such as Maria Eugênia, Pâdua, Luiz Augusta, Fernando Perillo, João Caetano and Marcelo Barra, considered by the magazine as “singers of the land” and, by us here named singers of “popular music from Goiás”, as true identity icons. Considering the movement, and to a certain extent, the biography of such artists, we sought to relate them to the cultural dynamics of the State of Goiás and its capital, Goiânia, between the years 1992 and 2013, under the strong impact of policies aimed at this sector. From this perspective, the research sought to investigate the extent to which the songs of such artists dialogue with the identity issues of the State, that is, with the construction of of the idea of Goianity orchestrated by institutions with the support of cultural policies. Recognizing the expressive character of the musical language, it was intended to distinguish the elements of the widespread identity, identifiers of the “Goiás way of being” pointed out by the movement. It was observed in such an exercise that in the elaboration of the idea of Goianity, elements related to the foundation of Goiânia - as a modern city - were and are articulated with elements of the tradition and the peasant experience of yore, common to the state’s history. In light of the work of these artists and cultural expressions, the “Movimento da Goianidade” systematized and expanded the identity narratives present in such songs, as well as in the music scene under which they expressed themselves. Under such movement, memories were triggered in the songs as mechanisms of construction and crystallization of an identity for the State, reverberating a kind of adjustment between a backward past and a modern, propagated present.